(untitled) (The Agriculturists, 2010)
The study was conducted at the Laboratory of the Department of Agronomy, Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur, during March to August, 2008 to examine the effect of hot water treatment at different temperatures with varying immersion periods on the viability of Sesbania rostrata seeds. Effect of dipping seeds in hot water at temperature of 78, 79, 80 and 810C for 24, 25, 26, 27 and 28 min were evaluated for this purpose. The lowest seed viability and seed germination (0.5%) was obtained at 81 0C for 28 min immersion period. The lowest hard seed (3.0%) and minimum (0.63%) pathogenic infection was found at same temperature and immersion period. Germination and tetrazolium tests were used throughout the experiment for estimating seed viability. Extreme hot water treatment deteriorated the viability of Sesbania rostrata seeds.